2018
DOI: 10.11613/bm.2018.020711
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Sigma metrics in four accredited Egyptian medical laboratories in some biochemical tests: an initiative towards sigma calculation harmonization

Abstract: IntroductionAnalytical quality is an essential requirement for best practice in any medical laboratory. Lack of a harmonized approach for sigma calculation is considered an obstacle in the objective comparability of analytical performance among laboratories adopting sigma metrics. It is urgently needed that all laboratory professionals interested in the analytical quality to work hard towards harmonization protocol for sigma calculation in order to properly select their analytical goals. This study aims at har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…21 It provides a feasible model for standardizing protocols and is being introduced to encourage all laboratories to use the same quality goals for their sigma metrics benchmarks. 22 Because TEa WS/T was more stringent than TEa CLIA for the most analytes, the σ WS/T was significantly lower than that of σ CLIA in 18 out of 19 assays (all except Na). Therefore, the limitation of selecting an appropriate TEa requirement for σ calculation should be considered.…”
Section: Discussionmentioning
confidence: 90%
“…21 It provides a feasible model for standardizing protocols and is being introduced to encourage all laboratories to use the same quality goals for their sigma metrics benchmarks. 22 Because TEa WS/T was more stringent than TEa CLIA for the most analytes, the σ WS/T was significantly lower than that of σ CLIA in 18 out of 19 assays (all except Na). Therefore, the limitation of selecting an appropriate TEa requirement for σ calculation should be considered.…”
Section: Discussionmentioning
confidence: 90%
“…If CV is less than 5%, then the particular method used for determination of an analyte’s concentration is said to have a very good performance& precise. 7,10,13 It can be visualised from Table1 & Table 2 that except for HDL, (CV%>5 in both L 1 & L 2 ) along with Total bilirubin & ALT (having CV%>5 in L 1 ); rest all parameters depicted CV<5%. This clearly indicates that our lab has achieved high level of precision in remaining 11 analytes.…”
Section: Discussionmentioning
confidence: 95%
“…The sigma symbol represents the ‘standard deviation’ in mathematical statistics, and its value usually reflects the testing quality level. 17 Six sigma represents a ‘world-class’ quality level, indicating that for every one million products (or services), only 3.4 defects can be detected, which is the expected quality goal. 17 The calculation of sigma depends on three variables: TEa, precision and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…17 Six sigma represents a ‘world-class’ quality level, indicating that for every one million products (or services), only 3.4 defects can be detected, which is the expected quality goal. 17 The calculation of sigma depends on three variables: TEa, precision and accuracy. TEa represents the quality goals selected by the laboratory, and previous studies have shown that there are significant differences in sigma levels for the quality goals used for the same analytes in the same laboratories.…”
Section: Discussionmentioning
confidence: 99%